Certificate of Accreditation for Master of Science ( Human Resource Development) - Universiti Malaysia Sarawak (Universiti Malaysia Sarawak, (UNIMAS), 2013)
Certificate of Accreditation for Master of Science ( Human Resource Development) has attained the quality assurance standards set by the agency and is in compliance with the Malaysian qualifications framework Level 7. Date of Accreditation : 11/09/2013